2022
DOI: 10.3389/fphar.2022.872988
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Serum Metabolites and Gut Microbiota in Diabetic Kidney Disease

Abstract: Disturbance of circulating metabolites and disorders of the gut microbiota are involved in the progression of diabetic kidney disease (DKD). However, there is limited research on the relationship between serum metabolites and gut microbiota, and their involvement in DKD. In this study, using an experimental DKD rat model induced by combining streptozotocin injection and unilateral nephrectomy, we employed untargeted metabolomics and 16S rRNA gene sequencing to explore the relationship between the metabolic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
4
18
0
Order By: Relevance
“…The gut microbiota has a symbiotic relationship with the host, involving energy metabolism, regulating the gut barrier, and maintaining immune responses (7). Many studies have consistently demonstrated (8)(9)(10)(11)(12) that changes in the composition of gut microbiota regulate the development of diabetes by inducing continuous low-grade inflammation and mediating the therapeutic effects of some type 2 diabetes mellitus(T2DM)drugs (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota has a symbiotic relationship with the host, involving energy metabolism, regulating the gut barrier, and maintaining immune responses (7). Many studies have consistently demonstrated (8)(9)(10)(11)(12) that changes in the composition of gut microbiota regulate the development of diabetes by inducing continuous low-grade inflammation and mediating the therapeutic effects of some type 2 diabetes mellitus(T2DM)drugs (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…16S rDNA, metagenomics, and mass spectrometry can be utilized to explore the diversity, composition, and function of gut microbiota as well as microbiota-related serum metabolites in patients with DKD. Interaction studies between plasma metabolomics and gut microbiome in experimental DKD mouse/rat model provided evidence for the gut-metabolism-kidney axis, and verified the involvement of gut microbiota and circulating metabolites in DKD progression (15,16). DKD patients displayed dysbiosis with composition, richness and diversity in gut microbiota (17)(18)(19).…”
Section: Gut Microbiota and Its Metabolites Gut Microbiotamentioning
confidence: 76%
“…Tryptophan is decomposed by bacterial tryptophanase into indole, which is a compound responsible for intercellular signal transduction, participating in the gene expression of intestinal epithelium connections and anti-inflammatory factors in intestinal epithelial cells, as well as maintaining host-microbiota homeostasis on the mucosa surface (51). As downstream critical metabolites, 3-(2-Hydroxyethyl) indole, 3-methylindole, and indoleacrylic acid were downregulated in the DKD model and were reinstated after treatment with Tangshen Formula (15). Some compounds produced by tryptophan metabolism are ligands for the aryl hydrocarbon receptor (AhR) and could induce AhR conformational changes.…”
Section: Tryptophanmentioning
confidence: 99%
“…Advances in previous metabolomics have discovered thousands of microbe-derived metabolites, some of which have been detected within host tissues, acting as communicator between host and microbiota. It has been reported that trimethylamine N-oxide (TMAO), polyphenols, protein-bound uremic toxins, and other metabolites had aggravated the progression of DKD [ 25 ]. However, there is no evidence to exclude the effect of IMP on DKD.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, as it comes to DKD, it commonly appears that Lactobacillus and Akkermansia reduce, leading to the decrease in short-chain fatty acids (SCFAs) [ 32 ]; conversely, Bacteroides , Paraprevotella , Oscillibacter , and Lachnoclostridium rise, leading to the increase in TMAO, LPS, phenyl sulfate (PS), and indoxyl sulfate (IS). SCFAs have been reported to have multiple beneficial regulatory roles in DKD through inhibiting oxidative stress and inflammation to recover renal function [ 25 , 33 ]. On the contrary, TMAO, LPS, PS, and IS have been suggested to contribute to renal dysfunction by activating the renin–angiotensin–aldosterone system (RAAS) and the endothelin system, and then inducing insulin resistance, inflammation, oxidative stress, and fibrosis [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%